Peningkatan Kemampuan Literasi Melalui Program Kampus Mengajar Angkatan 2 2021 - Abdurahman; Mila Agustini; Hany Novandina Maharani SY; Sakinatul Fajariyah (JURNAL ABDIMAS SERAWAI, 2022)
: One of the impacts of the Covid-19 in Indonesia has an impact on the world of education, especially in the field of literacy. The government, through the Directorate of Learning and Student Affairs, the Directorate General of Higher Education, prepares a teaching campus program that is part Independent Campus of Independent Learning(MBKM) and involves students in its implementation. Campus teaching activities focus on 1) Literacy and numeracy 2) Technology adaptation and 3) Assisting administration of school. The method of implementing this activity includes 1) preparation for implementation 2) Implementation stages and 3) Activity outputs. In the implementation of these campus teaching activities, schools that are still accredited C are greatly assisted, both in terms of teaching, assisting with administration, adapting technology, and especially in terms of student literacy so that it has increased.